Dilematika Shalat Fardhu di Awal Waktu - Irfan Fauzan (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2019)
In the phenomenon that occurs in today's society we often encounter about the dilemma of prayer in congregation, so from that we feel moved and want to explore further about fardlu prayers at the beginning of time by digging up data in the Qur'an and hadith as well as salafusshalih books. From the problems above, the writer tries to do a case study of problems that occur in our society. Nazir defines case study research as research on the status of a research subject that is pleased with a specific or typical phase of the whole personality. In this case, a teacher stops the KBM every day when the dhuhur adzan sounds and tells his students to go straight to praying even though the KBM hours are actually still long or not yet time to rest From the prayer dilemma at the beginning of time like this, finally I am interested to explore and try to formulate problems of several things related to Fardlu prayer at the beginning of time include: 1. Addressing the dilemma of Fardlu prayer at the beginning of time. 2. Whether or not delay fardlu prayer. 3. the category of people who are negligent in prayer. From the formulation of the problem above, the results can be stated as follows: Do not let the obligation of prayer and times as well as the limits that have been determined by syara 'both in terms of ease and importance cause us to get stuck in rigid, rigid and sacred thinking. Cases that are allowed to take precedence before prayer are a. When breaking the fast c. Eat prepared dishes even though it is prayer time d. Urinating takes precedence over prayer etc.